The Effect of Warning Letters and Forced Letters on the Disbursement of Tax Arrears at the South Makassar Pratama Tax Service Office - Muh Ainul Yaqin; Sitti Rahma Sudirman; Nurfiza Widayati; Yunita Fitria (Jurnal Riset Perpajakan: Amnesty, 2024)
This study aims to determine the effect of warning letters and forced letters on the disbursement of tax arrears at the South Makassar Primary Tax Service Office. The research employed documentation data collection techniques, gathering data on warning letters, forced letters, and the amount of arrears disbursement from 2020 to 2022 at the South Makassar Primary Tax Office. Data analysis was conducted using multiple linear regression analysis and partial tests. The results of the study revealed two key findings: (1) Warning letters have a positive but insignificant effect on the disbursement of tax arrears at the South Makassar Primary Tax Service Office; and (2) Forced letters have a positive and significant effect on the disbursement of tax arrears at the South Makassar Primary Tax Service Office. This indicates that while warning letters may raise awareness among taxpayers about their arrears, they do not significantly compel action towards disbursement. On the other hand, forced letters, which carry more severe consequences and legal implications, are more effective in prompting taxpayers to settle their arrears. The study underscores the importance of employing stronger enforcement measures to enhance tax compliance and improve the effectiveness of tax arrears recovery. Future research could explore the psychological and behavioral aspects of taxpayer responses to different enforcement actions, providing a deeper understanding of the mechanisms behind effective tax collection strategies. Additionally, expanding the scope of the study to include other regions and types of taxes could provide a more comprehensive view of the efficacy of warning and forced letters in various contexts.